The hermeneutics contribution to environmental bioethics faced with the biocentric versus anthropocentric dilemma in the globalization era - Aguirre Sala, Jorge Francisco (Acta Bioethica, 2015)
The aim of this essay is to show the contribution of hermeneutic philosophy to environmental bioethics faced with the biocentric versus anthropocentric dilemma. Biocentric means the radical unchanging conservation of nature, while anthropocentric means the exploitation and commercialization of earth with profit as the only limit. The hermeneutic philosophy is a method to unite and self-limiting these different horizons of value and meaning. Such method gathers through historic and conceptual location, the origin of each one of these conceptions and their respective thesis. Thanks to this, it applies the inclusion of key meanings, such as “earth”, “soil”, “ecosystem”, “environment” within a holistic notion of “biosphere”. With this it pretends to solve the problem and, moreover, to open the way to future research which could tackle the environmental bioethical dilemmas with the hermeneutic change of meanings with different values.